Nootropic Effects of Neolamarckia cadamba Leaves on Scopolamine-Induced Amnesia in Rats: Nootropic Activity of Neolamarckia Leaves in Rats - Mali, Kailas Krishnat; Salunkhe, Nitin Hindurao; Attar, Mahek Kadar; Mahajan, Niranjan Shishir; Dias, Remeth Jacky (Iranian Journal of Pharmaceutical Sciences, 2026)
This study evaluated the memory-enhancing potential of Neolamarckia cadamba (Roxb.) Bosser ethanolic extract (200 and 400 mg/kg, orally) in scopolamine-induced amnesic rats, with piracetam as a standard. Cognitive function was assessed using the elevated plus maze, hole board test, and Morris water maze, along with locomotor activity and brain acetylcholinesterase (AChE) levels. Phytochemical analysis revealed 0.515 g% phenolics (gallic acid equivalents) and 2.129 g% flavonoids (quercetin equivalents). GC–MS profiling identified 11 major bioactive compounds with reported antioxidant, anti-inflammatory, and neuroprotective activities. In vitro antioxidant evaluation by the DPPH assay demonstrated concentration-dependent radical scavenging, with an IC₅₀ of 337.42 µg/mL. Oral administration of N. cadamba extract for 14 days significantly reversed scopolamine-induced memory deficits. The extract reduced transfer latency in the elevated plus maze, shortened escape latency in the Morris water maze, and increased exploratory behavior in the hole board test. It also enhanced locomotor activity and decreased AChE levels, indicating improved cholinergic function. The high dose (400 mg/kg) consistently produced superior effects, suggesting dose-dependent efficacy. These findings suggest that N. cadamba ethanolic extract exhibits nootropic and neuroprotective effects, likely through antioxidant and cholinergic mechanisms, and may be a promising candidate for managing cognitive impairments, including Alzheimer’s disease.